BENEFITS OF MOTOR AND/OR COGNITIVE EXERCISE: A REVIEW WITH RECOMMENDATIONS FOR THE THIRD AGE - Mitja Gerževič; Matej Plevnik; Uroš Marušič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2017)
Physical activity in the form of aerobic and resistance exercise, leading to a high level of cardio-respiratory fitness represents a strong non-pharmacological preventive tool against cognitive decline and thus the occurrence of neuro-degenerative diseases in the third age. However, the effects are even greater if such exercise is performed on regular basis in the form of simultaneous combination of a motor and additional cognitive task, dancing or interactive video dancing or as a body-mind meditative exercise like Tai Ji Quan. The aim of this article is a review of benefits of motor/cognitive exercise with recommendations for older adults. In the first part, the benefits and effects of physical activity and exercise on cognitive functions are reviewed. Physical activity and exercise have an important role in mitigating age-related structural and behavioral changes within the brain, increases BDNF levels in the hippocampus, enhances learning and neurogenesis in the hippocampal regions and optimizes spatial abilities. The second part is expanded onto the benefits and effects of combined motor and/or cognitive exercise on cognitive functions with recommendations. This combination of motor and/or cognitive exercise could be achieved so that both activities are performed separately, one after another, named "motor and cognitive exercise" or simultaneously, named "motor-cognitive exercise". Based on this premise, we divided the second part into three sub-topics: i) the effects of physical exercise/training followed by computerized and other forms of cognitive training, ii) the effects of simultaneously performed motor and cognitive exercise/training and iii) the effects of dancing, interactive video dancing and ancient body-mind meditative techniques. Studies suggest that a combination of mental and physical training may result in greater cognitive gains, namely in larger improvements in the executive control task and in the paired-associates task.